2016
DOI: 10.1371/journal.pone.0152204
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Care for Pneumonia in Integrated Community Case Management: A Cross-Sectional Mixed Methods Study

Abstract: BackgroundPneumonia is the leading infectious cause of mortality in children under five worldwide. Community-level interventions, such as integrated community case management, have great potential to reduce the burden of pneumonia, as well as other diseases, especially in remote populations. However, there are still questions as to whether community health workers (CHW) are able to accurately assess symptoms of pneumonia and prescribe appropriate treatment. This research addresses limitations of previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…This study shows that while community health workers (CHWs) using four different RR counting devices are able to obtain respiratory rates (RR) from children in the majority of cases, the agreement of their measurements with the reference standard was low for all devices tested. As in previous studies in Zambia and Uganda, where expert clinicians were used as the reference standard to assess agreement with CHW measurements [8], [34], our study also shows a lot of variability between the CHWs and our automated reference standard RR count. Our data shows that it was especially difficult for CHWs to obtain an accurate count (± 2 breaths) in young infants, in which only 8% to 20% of the assessments were in agreement with the reference standard, regardless of the RR device used.…”
Section: Discussionsupporting
confidence: 75%
“…This study shows that while community health workers (CHWs) using four different RR counting devices are able to obtain respiratory rates (RR) from children in the majority of cases, the agreement of their measurements with the reference standard was low for all devices tested. As in previous studies in Zambia and Uganda, where expert clinicians were used as the reference standard to assess agreement with CHW measurements [8], [34], our study also shows a lot of variability between the CHWs and our automated reference standard RR count. Our data shows that it was especially difficult for CHWs to obtain an accurate count (± 2 breaths) in young infants, in which only 8% to 20% of the assessments were in agreement with the reference standard, regardless of the RR device used.…”
Section: Discussionsupporting
confidence: 75%
“…In the absence of doctors, front line health workers screen and diagnose diseases. In a study in Zambia, despite moderately high level of agreement between CHW classification of children with fast and normal breathing with that of experts, the limits of agreement were wide enough to lead the authors to conclude that further use of diagnostic tools such as POx would greatly help in assessing pneumonia in remote settings in LMIC [15]. On the other hand, there have been studies where inter observer agreement was found to be poor in RR measurements [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…This study did not aim at separating fever due to malaria from fever due to other reasons. The low validity of the HEWs’ classification of febrile conditions might be a result of errors both in performing clinical assessments and in interpreting the findings and classifying the illness . A previous Ethiopian study, however, showed that, given that the diagnosis was correct, the HEWs provided high‐quality care to sick children .…”
Section: Discussionmentioning
confidence: 99%